The Effect of Concentric and Eccentric Muscle Action on Muscle Stiffness at the Knee in Subjects With Spasticity of the Quadriceps - Hoessly, Margaret (Auckland University of Technology, 2003)
A higher than normal level of muscle stiffness is found in a wide variety of upper motor neurone disorders. This is reflected in elevated levels of resistance to lengthening of muscle often described as hypertonia or spasticity. Muscle weakness is also thought to be one of the major problems of motor function in many patients with these disorders. Another feature of the spastic condition is that of associated reactions, contraction of spastic muscle occurring on effort, especially in subjects with stroke. They appear to be the cause of a further increase in spasticity and a source of muscle shortening and joint contracture. To remedy muscle strength deficits patients should work at high levels of effort, however effort during treatment has been avoided by clinicians on the grounds that it would increase muscle stiffness and further hinder the patient’s motor performance. The present study was designed to investigate the effects of effort on spastic stiffness during concentric and eccentric muscle work of the quadriceps muscle. Nine subjects with significant spasticity of the quadriceps muscle participated in the study. Subjects undertook a modified ‘drop test’, using an isokinetic dynamometer that flexed the knee joint at 100 deg/sec, through a range of motion from 20 to 80 degrees prior to and after exercise. Force–angle ratios were used to calculate muscle stiffness in two parts of the range of motion, and electromyography (EMG) was used to monitor muscle activity both at rest and during the passive movement of the drop test. The exercise intervention involved 20 repetitions of concentric muscle work and 20 repetitions of eccentric muscle work performed on separate occasions at 75% of maximum voluntary muscle action (MVA). The results showed that under the conditions described above both resisted concentric and eccentric muscle work decreased stiffness (p < 0.05) of spastic muscle, there being no difference in effect between the two conditions. EMG of the quadriceps and hamstrings showed that there was no significant change in muscle activity (p < 0.05) at rest or during the ‘drop test’ following either concentric or eccentric contractions. This study demonstrated that effort occurring during resisted exercise did not increase muscle stiffness in spastic patients. Furthermore, there is some evidence to suggest that the decrease in stiffness resulted from change in the mechanical properties of the muscle. The findings are encouraging for clinicians as they support the therapeutic use of high levels of muscle work, which is the most efficacious means of increasing strength.
Keywords: Spasticity; Muscle strength -- Testing